Re: Which factors are associated with trainees' confidence in performing obstetric and gynecological ultrasound examinations? M. G. Tolsgaard, M. B. Rasmussen, C. Tappert, M. Sundler, J. L. Sorensen, B. Ottesen, C. Ringsted and A. Tabor. Ultrasound Obstet Gynecol 2014; 43: 444–451. (April 2014) - Gonçalves, L. F.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 444–451